Whistle-Blowing for Reward – Friend or Foe? Exploring a Possible Tax Whistle-Blowing Programme in South Africa - Monray Marsellus Botha; Carika Fritz (Obiter, 2019)
Tax evasion poses a serious threat to revenue collection. One way of obtaining information on taxpayers who fail to disclose certain sources of income for tax purposes is to use whistle-blowers. This article first considers whether the existing general regulatory framework pertaining to whistle-blowing in South Africa protects a whistle-blower from possible reprisals. Thereafter, whether an “evading” taxpayer’s right of access to information and to administrative justice may play a role in exposing a whistle-blower’s identity is reflected upon, as this may deter a person from blowing the whistle. The article further considers the contentious issue of whether a monetary or financial reward should be provided for tax whistle-blowers where previously undisclosed information regarding a taxpayer’s non-compliance is brought to light, and whether this would be in line with the existing general regulatory framework governing whistle-blowing. Finally, it is recommended that regulators in South Africa implement a whistle-blowing programme designed to reveal information about substantial misconduct, not only in financial markets, but also in matters regarding tax evasion; this would include a reward for the whistle-blower in the event of successful enforcement action.